2019
DOI: 10.1088/1757-899x/548/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Influence of Mixed Culture from Buried Soil Sample for Biodegradation of Sago Starch Filled Natural Rubber Latex Gloves

Abstract: The addition of sago starch into natural rubber (NR) latex compounds was aimed to accelerate the degradation process of the end products including gloves as an alternative to reduce solid waste disposal problem. In this research work, the degradation of sago starch filled natural rubber (SS/NR) latex gloves by a mixed culture from buried soil sample was investigated. The Gram staining test of mixed culture showed the Gram-negative bacteria are the dominant species as an effective bacterium to degrade the SS/NR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Recently, the use of monoculture, co-culture and consortium in rubber degradation studies, mimicking the natural environmental condition, has been compared [ 55 , 64 , 72 , 73 , 142 , 143 ]. The degradation of complex molecules is achieved through co-operative degradation where one organism transforms the original material into products that can be utilized by the other organisms [ 55 , 144 ]. The synergetic interaction of several strains of microorganisms in rubber degradation activity was better when compared to individual strains.…”
Section: Rubber Biodegradationmentioning
confidence: 99%
“…Recently, the use of monoculture, co-culture and consortium in rubber degradation studies, mimicking the natural environmental condition, has been compared [ 55 , 64 , 72 , 73 , 142 , 143 ]. The degradation of complex molecules is achieved through co-operative degradation where one organism transforms the original material into products that can be utilized by the other organisms [ 55 , 144 ]. The synergetic interaction of several strains of microorganisms in rubber degradation activity was better when compared to individual strains.…”
Section: Rubber Biodegradationmentioning
confidence: 99%
“…The global demand for rubber gloves keeps increasing despite the environmental problems related to their disposal [34]. Rubber gloves account for 24% of total medical solid waste [35]. Discarded NR gloves typically take at least two years to degrade in a natural environment.…”
Section: Environmental Concerns Related To Medical Glovesmentioning
confidence: 99%
“…In recent years, the widespread usage of rubber and the resulting large amount of waste of this material has increased interest in this field, with the objective of applying bioremediation. NR can be degraded by bacteria and fungi, but the process is slow and even slower in gloves with higher crosslinking densities [35,43]. Linos et al (2000) found that Pseudomonas aeruginosa AL98, a type of Gram-negative bacterium, was capable of disintegrating NR, in its natural form as NR latex concentrates or in its crosslinked forms as NR or IR gloves [44].…”
Section: Environmental Concerns Related To Medical Glovesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the widespread usage of rubber and the resulting large amount of waste of this material has increased interest in this field with the objective of applying bioremediation. NR can be degraded by bacteria and fungi, but the process is slow and even slower in gloves with higher crosslink densities [35,43]. Linos et al, (2000) found that Pseudomonas aeruginosa AL98, gram-negative bacteria, was capable of disintegrating NR, either in its raw form as NR latex concentrates or in its vulcanized forms as NR or IR gloves [44].…”
Section: Environmental Concerns Related To Medical Glovesmentioning
confidence: 99%